PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUCTURAL NUMBERED HEADS TOGETHER UNTUK MENINGKATKA HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII-A SMP NEGERI MINAS - Maharani, Putri Nabila; Syofni, Syofni; Solfitri, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is a classroom action research that aims to improve the learning process and improve student learning outcomes through the implementation of the Cooperative learning model of structured approach Numbered Heads Together. This research was conducted in class VII-A of SMP Negeri 2 Minas in the 2019/2020 odd semester school year. The subjects of this study were 25 students consisting of 12 male students and 13 female students. The study was done in two cycles with each cycle consisting of three meetings and one repetition every day. The research instrument used was a learning device and data collection instrument. Learning tools consist of syllabus, lesson plan, student work sheet and NHT question sheet. Data collection instruments consisted of observation sheets and learning outcomes tests. Based on the analysis of students and teacher activities after implementation of the Cooperative learning model of structured approach Numbered Heads Together, it can be concluded that there is an improvement of learning process. In quantitative analysis, On knowledge competence the percentage of students who can reach KKM on a basic score is 20% increased to 52% in Cycle I and increased to 64% in Cycle II. On skill competence, the percentage of students who can reach KKM on a basic score is 20% increased to 36% in Cycle I and increased to 56% in Cycle II. Based on the result, it can be concluded that the implementation of the Cooperative learning model of structured approach Numbered Heads Together can improve the learning process and the students’ mathematics learning outcomes in class of VII-A SMP Negeri 2 Minas. Key Words : Classroom Action Research, Cooperative Learning Model Of Structured Approach Numbered Heads Together, Mathematical Learning Outcomes